Evidence of protandry in Aa Rchb.f. (Orchidaceae, Cranichideae) - Trujillo, Delsy (Universidad de Costa Rica, 2011)
Protandry has been described in orchids since Darwin (1862) as a strategy to promote cross-pollination. Three different forms of protandry have been reported in tribe Cranichideae: downward movement of the labellum in Spiranthes species, upward movement of the column in Sauroglossum elatum Lindl. and Manniella spp., and downward movement of the column in Prescottia stachyodes (Sw.) Lindl. In the present work, through longitudinal and transverse sections of flowers of different developmental stages, we reported column movement of Aa erosa (Rchb.f.) Schltr. and the mechanism responsible for the movement. Our result shows that in an early flower stage (male phase), the column of Aa erosa is straight. The gradual cell death of the dorsal side of the column and size increase of the cells of the ventral side cause the column to bend downward to almost 90o representing the female stage. Some authors have suggested self-pollination in Aa. But flies exploring inflorescences of Aa species have been observed in the field by the author. This observation plus the evidence of protandry in Aa erosa could discard self- pollination as the only strategy of pollination in this genus.